2005
DOI: 10.3177/jnsv.51.231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Economic Status and Education Level on the Height and Weight of Community Adolescents in Nepal

Abstract: SummaryThere is scarce information on the relative importance of socio-economic fac tors in determining the adolescent anthropometric measurements. The objective of this study was to examine the effects of economic status, education level, and food consumption on the height and weight of community adolescents in Nepal. The study was done in the communities of the Kathmandu Valley area in Nepal. All together 426 unmarried adoles cent girls aged 14-19y were selected, The adolescents were interviewed regarding so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…One study showed that per capita food expenditure was positively associated with all nutritional status indexes . Likewise, SES, defined by a wide variety of indicators, was in 15 cases negatively associated with undernutrition or positively with nutritional status indexes . Household resources, including land holdings, possession of cattle, the number of living rooms, rented versus owned home, and housing type were negatively associated with undernutrition indicators or, to a lesser extent, positively with HA and WHZ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed that per capita food expenditure was positively associated with all nutritional status indexes . Likewise, SES, defined by a wide variety of indicators, was in 15 cases negatively associated with undernutrition or positively with nutritional status indexes . Household resources, including land holdings, possession of cattle, the number of living rooms, rented versus owned home, and housing type were negatively associated with undernutrition indicators or, to a lesser extent, positively with HA and WHZ .…”
Section: Resultsmentioning
confidence: 99%
“…86 Likewise, SES, defined by a wide variety of indicators, was in 15 cases negatively associated with undernutrition or positively with nutritional status indexes. 42,47,48,62,64,68,73,79,81,82,90 Household resources, including land holdings, possession of cattle, the number of living rooms, rented versus owned home, and housing type were negatively associated with undernutrition indicators 43,48,51,58,66,74 or, to a lesser extent, positively with HA and WHZ. 48,60 The lack of latrines (leading to open air defecation) and having a hand pump (instead of running water) were associated with BAZ.…”
Section: Individual Levelmentioning
confidence: 98%
See 1 more Smart Citation
“…According to WHO growth standards, children were considered malnourished (without pedal oedema) if one of the following statistical conditions were met [20,21]: Underweight: <−2 weight-for-age z-score. Wasting: <−2 weight-for-height z-score.…”
Section: Definitionsmentioning
confidence: 99%
“…Uno de los indicadores que mejor refleja las condiciones sociales y económicas de una población o un país es el crecimiento en talla (37,38). De hecho, el indicador talla para la edad se relacionó con disponibilidad de agua de acueducto y servicio sanitario, lo mismo que con el tamaño de la familia y el número de personas que duermen en la casa, mientras que el indicador peso para la talla no se relacionó con la disponibilidad de servicios sanitarios, pero sí con el tamaño de la familia y con los indicadores de hacinamiento.…”
Section: Des/no Desunclassified